Science: A Greatest Integer Function–A Punctuated, Cumulative Approach to the Inquisitive Nature of Science - Anor, Kristianne C. (Stance: an international undergraduate philosophy journal, 2012)
Thomas Kuhn argues that scientific advancements sometimes involve paradigm shifts between incommunsurable theories, thoughts, and concepts. I argue that the phenomenon Kuhn is attempting to describe is better explained as akin to a greatest integer function of punctuated equilibrium. I conclude that Kuhn is mistaken in thinking that science is an actively vigorous, cumulative discipline.